2016
DOI: 10.1159/000447446
|View full text |Cite
|
Sign up to set email alerts
|

Interaction with the MAPT H1H1 Genotype Increases Dementia Risk in APOE ε4 Carriers in a Population of Southern India

Abstract: Background: This study delineates the role of the interaction of apolipoprotein E (APOE) and MAPT alleles in contributing to disease risks of dementia in a southern Indian population. Methods: A sample of 419 patients comprising Alzheimer's disease (AD; n = 156), mild cognitive impairment (MCI; n = 87), frontotemporal dementia (FTD; n = 127), vascular dementia (VD; n = 37), and dementia with Lewy bodies (DLB; n = 12) was analysed in comparison with a control group (n = 138). APOE genotyping and MAPT haplotypin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…The initial search identified 721 references. Of those, 18 publications 21 38 with 2,004 cases and 3,705 controls were included in our meta-analysis. The study selection process was shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The initial search identified 721 references. Of those, 18 publications 21 38 with 2,004 cases and 3,705 controls were included in our meta-analysis. The study selection process was shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…MAPT encodes tau protein. Two moderate and one poor quality studies have reported significant association between MAPT H1 haplotype and DLB, but two good quality studies have not replicated this finding . Moreover, a moderate quality study has reported associations between PDD and MAPT H1 haplotype and another probably protective variant rs1467967…”
Section: Resultsmentioning
confidence: 99%
“…The APOE variants, especially its ε4 allele, are the most studied among all genetic variants in people with LBD . Apolipoprotein E (APOE) is involved in cholesterol mobilisation and redistribution during neuronal growth and injury, and it may promote β‐amyloid aggregation .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies or meta-analyses should consider evaluating the interaction between APOE polymorphism and other genetic variations involving individual differences in drug efficacy or the cholinergic system. In addition to CYP2D6 single nucleotide polymorphism rs1080985, future research can evaluate the interaction with other genetic variations such as the butyrylcholinesterase genotype, phosphatidylinositol-binding clathrin assembly protein (PICALM), paraoxonase 1 gene polymorphism, CHRNA7 genotype, and MAPT genotype [24,26,[48][49][50].…”
Section: Discussionmentioning
confidence: 99%